2016
DOI: 10.1155/2016/2825056
|View full text |Cite
|
Sign up to set email alerts
|

Cockroaches as a Source of High Bacterial Pathogens with Multidrug Resistant Strains in Gondar Town, Ethiopia

Abstract: Background. Cockroaches are source of bacterial infections and this study was aimed to assess bacterial isolates and their antimicrobial profiles from cockroaches in Gondar town, Ethiopia. Methods. A total of 60 cockroaches were collected from March 1 to May 30, 2014, in Gondar town. Bacterial species were isolated from external and internal parts of cockroaches. Disk diffusion method was used to determine antibiotic susceptibility patterns. Data were entered and analyzed by using SPSS version 20; P values <0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
49
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 17 publications
6
49
1
1
Order By: Relevance
“…1 This isolates are the main causes of a diverse type of community acquired and nosocomial infections, notably urinary tract infections, wound infections, respiratory tract infections, gastroenteritis, septicemia, pneumonia, biliary and peritoneal infections. 33 The isolation of higher rate (57.7%) of bacterial isolates from the external surface compared to gut (42.3%) of cockroach is consistent with other studies. 28,29 Tachbele et al and Ejimadu et al reported higher isolation of bacteria from gut of cockroach rather than from external surface.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…1 This isolates are the main causes of a diverse type of community acquired and nosocomial infections, notably urinary tract infections, wound infections, respiratory tract infections, gastroenteritis, septicemia, pneumonia, biliary and peritoneal infections. 33 The isolation of higher rate (57.7%) of bacterial isolates from the external surface compared to gut (42.3%) of cockroach is consistent with other studies. 28,29 Tachbele et al and Ejimadu et al reported higher isolation of bacteria from gut of cockroach rather than from external surface.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other studies. 19,33 Among antibiotic tested, all isolates were resistant to amoxycillin and amoxyclave, while more than half of isolates were resistant to doxycycline, nalidixic acid, ceftazidime, ciprofloxacin and ceftriaxone. However, imipenem and meropenem were relatively most effective antibiotic against the bacterial isolates.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These differences between 10d and 20d conditions could suggest that, even if the population is very stable along adult stages, it is being rearranged to its final composition. This rearrangement would imply a reduction in Fusobacterium and an increase of Ruminococcaceae along time (10d against 20d, Figure 3a).. On the other hand, Pseudomonas genus and an unclassified genus belonging to the family Pelagibacteraceae are more abundant only in metatranscriptomics analysis at 20d against 10d (Figure 3b).. Pelagibacteraceae has been described as a bacterial family localized in marine and freshwater environments [48], but has also been detected in the mouse gut microbiome [49] Pseudomonas genus has been related to pathogenicity in animals and plants, and is a commonly detected taxa in the gut of cockroaches [50]. These results suggest that these taxa increase their transcriptional activity but not their abundance in the population along time.…”
Section: Comparison Of Metagenomics and Metatranscriptomics/metaprotementioning
confidence: 99%
“…Insects have a wide distribution and can move freely between different environments; they may play an important role as reservoirs of drug-resistant strains and as their disseminators between animals and humans, especially when in contact with organic waste, livestock and their surrounding environment, and hospital facilities Mohammed et al, 2016;Schaumburg et al, 2016;Zhang et al, 2017;Onwugamba et al, 2018). In relation to insects caring antibiotic-resistant bacterial strains, studies have identified flies (Ahmad et al, 2011;Usui et al, 2015;Mohammed et al, 2016;Schaumburg et al, 2016;Zhang et al, 2017;Onwugamba et al, 2018) and cockroaches (Ahmad et al, 2011;Pai, 2013;Moges et al, 2016) as hosts of extended-spectrum beta-lactamase-and carbapenemase-producing Enterobacteriaceae, vancomycin-resistant E. faecium (VRE), and methicillin-resistant Staphylococcus aureus (MRSA). Insects collected from food establishments and in association PeerJ reviewing PDF | (2019:09:41227:1:1:NEW 18 Dec 2019)…”
Section: Introductionmentioning
confidence: 99%